Southern Thailand Peace Talks: The Long And Winding Road – An Analysis - Shafina Tantiana, Zulkipli (Universiti Malaysia Sarawak (UNIMAS), 2014)
When thinking about conflict in Thailand, people will tend to portray it through the street protest in Bangkok with people wearing specific colored T-shirts (Red and Yellow). Sad but true, less known about the long-simmering insurgency in the southern border provinces of Thailand, predominantly Pattani, Yala and Narathiwat. The intense political crisis that haunted Bangkok spawned negligence among the media on the complexity of the security situation in the forgotten south. Veritably, it can depict as a ‘covert war’ with less attention from the outside world. This working paper series discusses the current development of the Southern Peace Talks initiated by Yingluck Shinawatra’s government in early 2013, along the line analyze the challenges that stonewalled the move to install peace in the far south.